DIAGNOSIS OF ADHD SYNDROME BY COMPARITIVE ANALYSIS OF EEG SIGNALS OF BRAIN - R, Sunitha; Phaniraju, H B; Deepika, (The journal of contemporary issues in business and government, 2021)
One of the incurable mental disorder, which is estimated to occur in about of all the children (5-15 years, approximately 6.4 million), is Attention Deficit Hyper Active Disorder (ADHD). Electroencephalogram (EEG) is a best method for monitoring, recording and measuring spontaneous voltage fluctuations of the brain that caused due to the ionic current associated with the neurons. Due to having many advantage of using EEG over MRI, PET and MEG in the detection and diagnosis of ADHD, we presented the comparative analysis and distance measure techniques for detection and classification of this disorder in the childhood. In comparative analysis, we compare different parameters of EEG signals of ADHD affected children with normal children. An algorithm is developed to classify the children effectively as normal or affected.